Reintegration of Former Offenders or the Path to Recidivism (Criminal Reoffending) - Karović, Sadmir (Zbornik Instituta za kriminološka i sociološka istraživanja, 2024)
In this paper, the author aims to address and problematize the adequacy of the criminal enforcement system in terms of the social adaptation and reintegration of convicted persons after serving a prison sentence, as well as to critically examine the potential problems and risks faced by this population. The humanization of the criminal enforcement system requires respect for the personal integrity and dignity of each individual, along with the implementation of appropriate programs and treatments aimed at behavior change and raising awareness about the harmful effects of criminal activity to achieve specific objectives. In this context, the legislator has prescribed a catalog of rights and established certain rules of conduct, particularly for specific categories, such as minors, individuals with mental disorders, persons with disabilities, and drug users. Special attention is given to juveniles due to their age, criminal-legal status, and the potential risk of recidivism (criminal reoffending), with a particular focus on sentencing and the execution of juvenile imprisonment. Accordingly, the paper centers on the social adaptation and reintegration of former offenders, with a particular focus on the real problems and challenges they face after serving their sentences and being released from correctional institutions.